Analisis Kinerja Keuangan Terhadap Nilai Perusahaan Sektor Energy Yang Terdaftar Di Bursa Efek Indonesia - Valadeva Izzulhaq; Bayu Kurniawan; Rita Meiriyanti (Yayasan Al Ma'arif Dawuhan, 2025)
This study explores the relationship between financial performance and company value in the energy sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The goal is to assess how various financial performance indicators impact firm value, as measured by the Price to Book Value (PBV). The financial performance indicators used in this study include Current Ratio (CR), Return on Assets (ROA), Return on Equity (ROE), Total Asset Turnover (TATO), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and firm size (Size). To examine this relationship, the study employs panel data regression, using data sourced from the IDX and analyzed with Excel and E-Views software. This methodology helps identify the degree to which financial performance metrics influence company value in the energy sector. The results reveal that certain financial indicators significantly impact company value. Specifically, ROA, TATO, and DAR were found to have a meaningful effect on PBV during the 2020–2023 period. These findings suggest that the efficiency of asset management, the ability to generate profits from assets, and the level of debt relative to assets play critical roles in determining a company’s value. Conversely, other factors such as CR, ROE, DER, and firm size did not show a significant relationship with PBV during the study period. This study highlights the importance of selecting the right financial performance metrics when evaluating the value of companies in the energy sector, offering valuable insights for investors, analysts, and corporate managers aiming to optimize firm performance and valuation.